Langmuir solitons in plasma with κ-deformed Kaniadakis distributed electrons in the kinetic regime - Suyun Zhou; Hui Chen (AIP Advances)
The dynamics of Langmuir solitons in plasma with κ-deformed Kaniadakis distributed electrons is studied. First, a Zakharov-type equation describing the evolution of the fields of Langmuir and ion-acoustic wave is derived in a kinetic regime. Then, in the one-dimensional case, the Zakharov-type equation is reduced to the well-known nonlinear Schrödinger equation that is applied to investigate the characteristics of modulated Langmuir wave packets. It is shown that there are two types of solitons, one is bright soliton in the subsonic regime and the other is dark soliton in the supersonic regime. It also found that when the amplitudes of both types of solitons are fixed, the width of bright soliton increases, while the width of dark soliton decreases, with increased distribution index κ. The present work may serve as a preliminary investigation into the nonlinearity of the κ-deformed Kaniadakis distributed plasma system.